Situation of Working Slum Children in Dhaka City - Farah, Shayela; Karim, Mohoshina; Afrin, Sharmina (Delta Medical College Journal, 2019)
Background: Rapid urbanisation in the 20th century has been accompanied by the development of slums. Nearly one-third of the world’s population and more than 60% of urban population in the least developed countries live in slums, including hundreds of millions of children. Slums are areas of broad social and health disadvantage to children and their families due to extreme poverty, overcrowding, poor water and sanitation, substandard housing, limited access to basic health and education services. Objective: To assess the demographic and nutritional situation of working slum children in Dhaka city. Materials and method: This descriptive cross sectional study was conducted at Moghbazar slum situated in Dhaka city from July to December, 2015. Results: Out of 200 slum children, 57 (28.5%) were in the age group of 12-14 years, among them 110 (55.0%) were male. Regarding educational background, more than fifty percent never attended any kind of school. Forty five percent respondents lived with their parents. About 26% of the slum children were engaged in beggary, 23% were van/rickshaw puller, 22% were tokai, and 10% were cooli. Near about 75% respondents did medium type of work and 80% did 5-8 hour work per day and most of their income was 500-800 Tk. per month. One third respondents were severe under nourished, 50 (25%) were normal and 30 (15%) respondents were obese. Conclusion: Increasing numbers of slums constitute a major challenge to development. Therefore, health related programmes should focus to improve the overall wellbeing of the working slum children. Delta Med Col J. Jan 2019 7(1): 26-30